"A magical little pill that will relieve you of your womanly issues": What young women say about menstrual suppression. Issue 1 (1st January 2016) - McMillan, Colleen; Jenkins, Amanda
Abstract : Perceptions of menstruation by media discourses portray this bodily function to be messy, inconvenient, and as an unnecessary phenomenon to be controlled or possibly eliminated. Commercials shown on YouTube targeted toward young women suggest that having a monthly period is not healthy and a lifestyle that is menses free is both pharmacologically available and recommended in order to live a fuller life. We explored the meanings attached to online menstrual suppression commercials with 10 women aged between 18 and 25. In-depth open-ended interviews were conducted over a 10-month period in 2014 after each participant viewed three menstrual suppression online advertisements. Feminist critical discourse was used for analysis with both authors coding for inter-rater reliability recognizing how our age difference and relationship as mother and daughter informed our interpretation. An overarching theme of tension emerged from the interviews with participants feeling detached due to the gendered stereotypes the commercials used to frame menstruation as compared to their own lived experience. Meanings associated with the menstrual suppression commercials were contrary to the participants' lived experience of menstruation as a healthy process not a detrimental one to their well-being as suggested by the commercials. Subliminal messages within the advertisements were identified as reinforcing gender bias and prejudices, including those associated with femininity. Despite attempting to emulate popular culture, the menstrual suppression advertisements were largely dismissed by this group of participants as undermining their intelligence and of intentionally creating divisive binaries between groups of women. This study suggests that historical bias and stereotypical prejudices were identified by this group of young women within the marketing of menstrual suppression products and, as such, were dismissed as inauthentic to the menstruation experience reflecting a form of menstrual activism.